Pengaruh Model Pembelajaran Terhadap Hasil Belajar Matematika Ditinjau Dari Motivasi Belajar Siswa - Upu, Hamzah; Intang, Baso; Akhmad, Hartina (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2018)
The purposes of the research were to describe and analysis of : (1) influence of learning interaction with learning motivation to mathematics learning achievement, (2) For high learning motivation, is there any differents mathematics learning achievement with uses CRH and NHT, (3) For low learning motivation, is there any differents mathematics learning achievement with uses CRH and NHT. The design of the research, was Quasi Experimental. The population in this research are all of VIII in the even semester of SMPN 1 Pallangga and SMPN 3 Sungguminasa academic year 2017-2018. The sampling of this research are one class in every schools. The samples of this research is cluster double random sampling. The method of collect the data used questionnaire, observation and test. The technique of data analysis used is the technique descriptive and inferential statistical analysis. The results analysis of this research are: (1) no influence of learning interaction with learning motivation to mathematics learning achievement, (2) For high learning motivation, there are differents mathematics learning achievement with uses CRH and NHT (81,66 > 72,22), (3) For low learning motivation, there are differents mathematics learning achievement with uses CRH and NHT (78,88 > 74,44).